Mutational analysis of gap junction formation. - Dahl, G (1992)
The paired oocyte cell-cell channel assay was used to investigate the mechanisms involved in the process of formation of gap junction channels. Single oocytes, injected with connexin-specific mRNAs, accumulate a pool of precursors from which cell-cell channels can form rapidly upon pairing. Several lines of evidence, including immunohistochemistry and surface labeling, indicate that part of this precursor pool is located in the cell membrane, probably in the form of closed hemichannels. The homophilic binding of hemichannels to each other can be mimicked by synthetic peptides representing the extracellular loop sequences of connexin32. The peptides specifically suppress channel formation. A crucial role is established for the six cysteines in the extracellular domains that are conserved in all vertebrate gap junction proteins. Change of any of these cysteines into serines results in absolute loss of function of the mutant connexin. The effects of thiol-specific reagents on channel formation suggest that docking and/or opening of channels involves disulfide exchange. Several of the variable amino acids in the extracellular loop sequences were found to determine specificity of connexin-connexin interactions.